TANAH WAKAF TERLANTAR (PERSPEKTIF PP NOMOR 11 TAHUN 2010) - Hidayati, Tri (LP2M IAIN Palangka Raya, 2011)
The existence of Government Regulation number 11 of 2010 about the Control and the Utilization of Neglected Land is a reformation step of agrarian to implement the Constitution of 1945 in article 33: verses 3. The objects of the regulation include the land that has been given by the government such the proprietary rights (Hak Milik), building rights (Hak Guna Bangunan) and enterprise rights (Hak Guna Usaha), use (Hak Pakai) and management rights (Hak Pengelolaan) or land that is not used appropriately or utilized effectively. The phenomena related to waqf land are so apprehensive. The numbers of the waqf lands reaches 2, 7 M2 (data from BWI or Indonesian Waqf Board in 2009). However, related to the status of the waqf lands which are permanent as in the article 40 of Waqaf Regulation, the neglected waqf lands cannot be utilized as waqf land as the objects of the control to be taken over by the government. To over the problem, ideally, the function of the waqf land should be productive in line with the article 44 of Waqf Law jonctu article 48 of Government Regulation nomor 42 of 2006 about the Implementation of Waqf Law and it is of course, all depend on nazhir (waqf land administrators).